IoT and WSN applications for modern agricultural advancements emerging research and opportunities - Mukherjee, Proshikshya, 1992-; Pattnaik, Prasant Kumar, 1969-; Panda, Surya Narayan (Advances in wireless technologies and telecommunication (AWTT) book series., 2019)
"This book explores the development of effective data computing operations on agricultural advancement that are fully supported by the Internet of Things, cloud computing, and wireless sensor network systems"--